Microtubule actin crosslinking factor 1 promotes osteoblast differentiation by promoting β‐catenin/TCF1/Runx2 signaling axis. Issue 2 (3rd August 2017) - Hu, Lifang; Su, Peihong; Yin, Chong; Zhang, Yan; Li, Runzhi; Yan, Kun; Chen, Zhihao; Li, Dijie; Zhang, Ge; Wang, Liping; Miao, Zhiping; Qian, Airong; et al.
Abstract : Osteoblast differentiation is a multistep process delicately regulated by many factors, including cytoskeletal dynamics and signaling pathways. Microtubule actin crosslinking factor 1 (MACF1), a key cytoskeletal linker, has been shown to play key roles in signal transduction and in diverse cellular processes; however, its role in regulating osteoblast differentiation is still needed to be elucidated. To further uncover the functions and mechanisms of action of MACF1 in osteoblast differentiation, we examined effects of MACF1 knockdown (MACF1‐KD) in MC3T3‐E1 osteoblastic cells on their osteoblast differentiation and associated molecular mechanisms. The results showed that knockdown of MACF1 significantly suppressed mineralization of MC3T3‐E1 cells, down‐regulated the expression of key osteogenic genes alkaline phosphatase (ALP), runt‐related transcription factor 2 (Runx2) and type I collagen α1 (Col Iα1). Knockdown of MACF1 dramatically reduced the nuclear translocation of β‐catenin, decreased the transcriptional activation of T cell factor 1 (TCF1), and down‐regulated the expression of TCF1, lymphoid enhancer‐binding factor 1 (LEF1), and Runx2, a target gene of β‐catenin/TCF1. In addition, MACF1‐KD increased the active level of glycogen synthase kinase‐3β (GSK‐3β), which is a key regulator for β‐catenin signal transduction. Moreover, the reduction of nuclear β‐catenin amount and decreased expression of TCF1 and Runx2 were significantly reversed in MACF1‐KD cells when treated with lithium chloride, an agonist for β‐catenin by inhibiting GSK‐3β activity. Taken together, these findings suggest that knockdown of MACF1 in osteoblastic cells inhibits osteoblast differentiation through suppressing the β‐catenin/TCF1‐Runx2 axis. Thus, a novel role of MACF1 in and a new mechanistic insight of osteoblast differentiation are uncovered. Abstract : Knockdown of MACF1 dramatically reduced the nuclear translocation of β‐catenin, decreased the transcriptional activation of T cell factor 1 (TCF1), and down‐regulated the expression of TCF1, lymphoid enhancer‐binding factor 1 (LEF1), and Runx2, a target gene of β‐catenin/TCF1. In addition, MACF1 knockdown increased the active level of glycogen synthase kinase‐3β (GSK‐3β), which is a key regulator for β‐catenin signal transduction. Moreover, the reduction of nuclear β‐catenin amount and decreased expression of TCF1 and Runx2 were significantly reversed in MACF1‐KD cells when treated with lithium chloride, an agonist for β‐catenin by inhibiting GSK‐3β activity. Taken together, these findings suggest that knockdown of MACF1 in osteoblastic cells inhibits osteoblast differentiation through suppressing the β‐catenin/TCF1‐Runx2 axis. Thus, a novel role of MACF1 in and a new mechanistic insight of osteoblast differentiation are uncovered.